Innovative Aspects of the Providing Competitiveness of Enterprises - Ямненко, Г. (Київський національний університет імені Тараса Шевченка, 2016)
Світовий досвід економічного розвитку свідчить, що каталізатором модернізації й структурної перебудови економіки країни є інновації, які сприяють посиленню конкурентоспроможності, прибутковості та інноваційного розвитку підприємств, допомагають завойовувати нові й утримувати існуючі ринки. Вирішення проблем активізації інноваційної діяльності підприємств стає головною запорукою забезпечення успіху ринкових реформ. У результаті дослідженнявизначено конкурентні переваги, пов'язані з інноваційною діяльністю. Обґрунтовано, що утримання стійкої конкурентної позиції на ринку залежить від визначення та підтримання ключових чинників успіху. Запропоновано основні етапи забезпечення конкурентоспроможності підприємства на основі використання його інноваційних можливостей. Показано, що тільки розвиваючи існуючі та формуючи нові конкурентні перевагипідприємство зможе досягти бажаного стану конкурентоспроможності у сучасних реаліях. Для забезпечення конкурентоспроможності підприємств пропонується формувати ефективну конкурентну стратегію шляхом широкого використання інноваційних рішень на основі знань. Основою конкурентних переваг слід вважати процес стимулювання інновацій.

The world experience of economic development shows that innovations are the catalyst of modernization and restructuring of the economy, which contributedthe strengthening of the competitiveness, profitability and innovative development of enterprisesand help to conquer new and retain existing markets. The decision of problems of activation of innovative activity of enterprises becomes the main guarantee of providing of success of market reforms. The purpose of this article is to determine of features of intercommunication between innovative activity and competitive advantages of an enterprise. The study identified the competitive advantages related to innovative activity. It is proved that the maintenance of sustainable competition position at the market depends on determination and maintenance of key success factors. It is determined the basic stages of providing of competitiveness of an enterprise through the use of its innovative capabilities. It is shown that only through developing existing and creating new competitive advantages an enterprise will be able to attain the desired state of competitiveness in the modern realities. It has suggested forming an effective competitive strategy through extensive use of innovative decisions on the basis of knowledge for providing of competitiveness of enterprises. The basis to competitive advantages should be considered the process of stimulation innovations.
Інноваційні аспекти забезпечення конкурентоспроможності підприємств
Keywords: інноваційна діяльність; знання; конкурентоспроможність підприємств; конкурентні переваги; innovative activity; knowledge; competitiveness of enterprise; competitive advantages